CALCULATION OF VIETNAM’S COASTLINE LENGTH (MAINLAND) BASED ON TOPOGRAPHIC MAP SYSTEM AT SCALE 1/50,000 - Dung, Bui Quang; Khanh, Uong Dinh (Vietnam Journal of Marine Science and Technology, 2016)
Several values of Vietnam’s coastline length were obtained by a number of organizations and foreign offices. This situation is mainly dependent on sources of data, measurement technique, and many other problems. This calculation is made with digital national topographic maps at scale 1/50,000 as source data for coastline extraction including river mouths, bays but lagoons and island coasts. The measurement was made using 200 m and 1,000 m strait length as base units, with appropriate technique. The calculation can provide scientific values of the coastline length of Vietnam as well as coastal provinces. As the result, Vietnam coastline length (mainland) is of 3,658 km and 3,289 km at the base unit of 200 m and 1,000 m, respectively.